EVALUATION OF AGRICULTURAL SOIL HEALTH INDEX FOR SUSTAINABLE NUTRIENT MANAGEMENT IN ARMORI OF GADCHIROLI DISTRICT (M.S.) - Chavhan H.R,; BorkarP. R., (The Bioscan, 2025)
Present study has been conducted in the Armori region of Gadchiroli district, during December 2024 to February 2025, for assessments of soil fertility and microbial populations. Nine soil samples were collected from three villages (V1, V2, V3) and analyzed for pH, organic carbon, macronutrients (N, P, K, S), and micronutrients (Zn, Mn, Fe, Cu). Soil pH ranged from 5.2 to 7.85, with Waghada Burdi (V2) having the highest pH. Electrical conductivity varied from 0.08 to 0.22 dS/m, and nitrogen levels ranged from 275 kg/ha in Arsoda to 310 kg/ha in Waghada Burdi. The Soil Health Index (SHI) ranged from 0.30 to 0.65, with Waghada Burdi showing the best soil health. The SHI, which integrates soil organic carbon, pH, conductivity, nutrient content, and microbial activity, revealed nutrient imbalances requiring targeted nutrient management interventions. The study highlights the importance of site-specific strategies, including organic practices, balanced fertilization, and soil conservation, to enhance productivity and ensure sustainable agriculture in the region.